Association between Manganese Superoxide Dismutase (MnSOD Val-9Ala) genotypes with the risk of generalized aggressive periodontitis disease - Kazemi, E; Moradi, M-T; Yari, K; Mousavi, S A R; Kahrizi, D (Cellular and Molecular Biology, 2015)
Generalized aggressive periodontitis (GAP) is a subtype of periodontal diseases that characterized by rapid destruction of periodontal supporting tissues. The MnSOD Val-9Ala mutation of manganese superoxide dismutase gene (MnSOD Val-9Ala) and its correlation with periodontal diseases has been studied in different populations. The purpose of this study was to investigate the possible association of MnSODVal-9Ala polymorphism with periodontitis disease in sample of GAP patients in Iran for the first time. Following a GAP examination, 50 GAP patients and 100 healthy individuals were recruited. Genomic DNA was extracted from peripheral blood leukocytes and the MnSODVal-9Ala polymorphismwas detected using PCR-RFLP method. The frequency of Ala/Ala, Ala/Val and Val/Val genotypes in healthy individuals were 25, 66 and 9%, respectively. In periodontitis patients, frequencies were as Ala/Ala (12%), Ala/Val (50%) and Val/Val (38%) genotypes. There was a significant positive association between distribution of MnSOD Val-9Ala genotypes and the risk of periodontitis disease (p<0.05). Our results indicated that MnSOD Val-9Ala gene polymorphism has a positive association with the risk of periodontitis disease.